The effect of mimicking febrile temperature and drug stress on malarial development - Adisakwattana Poom; Mungthin Mathirut; Udomsangpetch Rachanee; Na-Bangchang Kesara; Somsri Sangdao; Aunpad Ratchaneewan; Chaijaroenkul Wanna (BMC, 2009)
Abstract Background Malaria remains one of the most important tropical diseases of human with 1-2 million deaths annually especially caused by P. falciparum. During malarial life cycle, they exposed to many environmentally stresses including wide temperature fluctuation and pharmacological active molecules. These trigger malarial evolutionarily adaptive responses. The effect of febrile temperature on malarial growth, development and drug susceptibility by mimicking patient in treatment failure before and after drug uptake was examined. Methods Sensitivities of P. falciparum to antimalarial drug (chloroquine, mefloquine, quinine and artesunate) were investigated based on the incorporation of [3H] hypoxanthine into parasite nucleic acids or radioisotopic technique. The number of parasites was examined under microscope following Giemsa staining and the parasite development at the end of each phase was counted and comparison of parasite number was made. The proteome was separated, blotted and hybridized with anti-Hsp70s primary antibody. The hybridized proteins were separately digested with trypsin and identified by MALDI-TOF peptide mass fingerprint. Results The results show that febrile temperature is capable of markedly inhibiting the growth of field isolate P. falciparum but not to K1 and 3D7 standard strains. K1 and 3D7 grown under heat shock developed greater and the reinfection rate was increased up to 2-folds when compared to that of non-heat shock group. The IC50 value of K1 toward chloroquine, mefloquine and quinine under heat shock was higher than that of K1 under non-heat shock which is opposite to that of 3D7. Heat shock caused death in field isolated parasite. It was also found that the febrile temperature coped with chloroquine uptake had no effect to the development, drug sensitivity and the parasite number of K1 strain. In the opposite way, heat shock and chloroquine shows extremely effect toward 3D7 and field isolate PF91 as shown by higher number of dead parasites compared to that of control group. After culture under high temperature with artesunate, the total parasite number of all strains including K1, 3D7 and PF91 was extremely decreased and the parasite was not found at the end. Additionally, the expression of pfHsp70s was found in all strains and conditions as shown in 120 kDa hybridized band. However, the proteome extracted from K1 grown under heat shock with chloroquine, anti-pfHsp70 interacted with additional three bands identified by MALDI-TOF as elongation factor-1α (83 kDa), pfHsp86 (60 kDa) and phosphoethanolamine N-methyltransferase (43 kDa). Conclusion In conclusion, febrile temperature was capable of markedly inhibiting the growth of field isolate P. falciparum while the development, reinfection rate and drug (chloroquine, mefloquine and quinine) resistant level of standard strain K1 was enhanced. However, the febrile temperature coped with chloroquine had no effect to the development, drug sensitivity and the parasite number of K1 strain. In the opposite way, heat shock and chloroquine showed extremely effect toward 3D7 and field isolate PF91 as shown by some died parasites. Heat shock protein 70 (pfHSP70) of strain K1 under heat shock with chloroquine might involved in many pathways in order to sustain the parasite.